Preparation method of low-precipitation low-volatility polyester film

By adding dipentaerythritol phosphate in the polycondensation stage of the polyester film, the problem of low molecular weight precipitation of polyester films under high temperature and/or high humidity conditions is solved, which significantly reduces the haze improvement and is suitable for areas with high optical performance requirements.

CN119659054APending Publication Date: 2025-03-21FOSHAN MAILA HONGJI FILM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411866123.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing polyester films are prone to precipitation of low molecular weight substances under high temperature and/or high humidity conditions, resulting in increased haze and limiting their application in the field of colorless and transparent.

Method used

A small amount of dipentaerythritol phosphate is added at a specific stage of polycondensation, which reduces the production of low molecular weight substances by increasing the crosslinking degree and antioxidant properties of the system.

Benefits of technology

It significantly improves the haze increase of polyester films in high temperature and/or high humidity conditions, maintains the stability of other properties, and is suitable for areas with high optical performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005194382820000061
    Figure BDA0005194382820000061
Patent Text Reader

Abstract

The invention relates to a preparation method of a low-precipitation low-volatility polyester film, which comprises the following steps: esterifying a diol monomer and an aryl diacid monomer in the presence of a catalyst, then carrying out vacuum polycondensation, adding dipentaerythritol phosphate which accounts for 0.5-0.8 wt% of the mass of the diol monomer when the intrinsic viscosity of a system product reaches 0.52-0.57 dL / g in the polycondensation stage, and carrying out vacuum polycondensation to obtain the low-precipitation low-volatility polyester film. Performing post-treatment to obtain a core layer polyester raw material; the core layer polyester raw material and the surface layer polyester raw material are respectively added into a melt extruder for three-layer co-extrusion, and then the ABA type three-layer composite structure polyester film is obtained through two-way stretching. After the polyester film obtained by the preparation method is subjected to high temperature and / or high humidity, the haze improvement value is very low. The method is very suitable for the field with high optical performance requirements. The preparation method provided by the invention can be completed on the basis of original polyester master batch synthesis equipment, does not need to add extra large expensive equipment and process, and has the advantage of industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester films, and in particular relates to a method for preparing a low-precipitation and low-volatile polyester film. Background Art

[0002] During the downstream processing of ordinary transparent polyester film, low molecular weight substances usually volatilize and precipitate due to the influence of heating process. The precipitates stay on the surface of the film, causing the film surface to become foggy and the haze index to increase. There are several methods in the prior art to reduce precipitation. One is to add stabilizers, but the addition of stabilizers often has an adverse effect on the optical properties or mechanical properties of polyester films; there is also a technology to organize the precipitation of low molecular weight substances inside the film by adding a coating barrier layer or vacuum sputtering a dense metal coating. The coating barrier layer requires a thicker coating, and the actual application effect is poor; vacuum sputtering increases the manufacturing cost, and the metal coating is generally colored, which limits the application of polyester film in the field of colorless and transparent. Polyester films with poor volatility and precipitation are manifested in the appearance that under high temperature and / or high humidity conditions, low molecular weight substances will migrate from the inside to the surface, resulting in whitening and blurring of the polyester film surface, which is manifested as a significant increase in haze. In particular, the application of polyester film as an ITO conductive film or other films with high optical performance requirements is limited.

[0003] CN114163672A discloses a low precipitation polyester film and a preparation method thereof; the polyester film comprises a polyester base film and a low precipitation coating coated on the surface of the polyester base film, the low precipitation coating is obtained by coating and curing a water-soluble coating liquid, and the water-soluble coating liquid of 100 mass fraction comprises 4-12 mass parts of a water-soluble resin, 85-95 mass parts of deionized water, 0.5-3 mass parts of a cross-linking agent and 0.1-0.3 mass parts of a surfactant. To achieve appropriate low precipitation performance, the coating liquid is relatively thick, generally needing to be more than 2μm, which affects other properties of the film.

[0004] By analyzing the sources of low-volatile, easily migrated and precipitated small molecules, polyester film production generally adopts melt co-extrusion. At a higher extruder operating temperature, polyester chips may undergo intramolecular chain scission to produce low molecular weight fragments, or produce low molecular weight substances during aging tests. There is an existing technology for secondary polymerization to increase the molecular weight of polyester and reduce small molecular weight fragments, but the equipment required for this secondary polymerization is expensive and not suitable for large-scale industrial production.

[0005] Therefore, it is necessary to develop a polyester film preparation process that relies on existing polyester film production technology to obtain a polyester film with low precipitation and low volatility without affecting other properties. Summary of the invention

[0006] In order to overcome the defect of polyester film in the prior art that haze is easily increased under high temperature and / or high humidity conditions, the present invention proposes a method for preparing a low-precipitation and low-volatility polyester film. By adding a small amount of dipentaerythritol phosphate at a specific stage of polycondensation, the phenomenon of increased haze of the polyester film under high temperature and / or high humidity conditions is significantly improved without affecting other properties of the polyester film. Specifically, the present invention provides the following technical solutions:

[0007] A method for preparing a low-precipitation and low-volatile polyester film comprises the following steps:

[0008] (S1) esterifying the diol monomer and the aromatic diacid monomer in the presence of a catalyst, followed by vacuum polycondensation, and in the polycondensation stage, when the intrinsic viscosity of the system product reaches 0.52-0.57 dL / g, adding 0.5-0.8 wt% of dipentaerythritol phosphate by weight of the diol monomer, and obtaining a core layer polyester raw material after post-treatment;

[0009] (S2) 80-90wt% of silicon-containing opening agent polyester chips and 10-20wt% of acrylic resin are melt-extruded and post-treated to obtain a surface polyester raw material;

[0010] (S3) adding the core layer polyester raw material and the surface layer polyester raw material into a melt extruder respectively, and performing three-layer co-extrusion to obtain an ABA type three-layer composite structure polyester masterbatch, wherein A is the surface layer polyester and B is the core layer polyester;

[0011] (S4) Pre-crystallization, drying, longitudinal and transverse biaxial stretching, heat setting, relaxation, cooling, pulling, and winding of the composite structure polyester masterbatch are performed to obtain a low precipitation and low volatility polyester film.

[0012] Further, in step (S1), the diol monomer is selected from at least one of hexylene glycol, cyclohexanediol, ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, and neopentyl glycol, and the aromatic diacid monomer is selected from at least one of terephthalic acid, naphthalene dicarboxylic acid, and biphenyl dicarboxylic acid. Further, the molar ratio of the diol monomer to the aromatic diacid monomer is 1-1.2:1-1.2, preferably the molar ratio of the diol monomer to the aromatic diacid monomer is 1:1-1.2.

[0013] Further, in step (S1), the catalyst is selected from antimony catalysts (antimony trioxide, antimony acetate), titanium catalysts (tetrabutyl titanate, tetraethyl titanate, tetrapropyl titanate and tetraisopropyl titanate), germanium catalysts (tetragonal germanium dioxide), tin catalysts (monobutyl tin oxide, monobutyl tin triisooctoate, stannous octoate, dibutyl tin diacetate, dibutyl tin dilaurate). Preferably, it is a mixed catalytic system of germanium catalysts and titanium catalysts; more preferably, the mass ratio of germanium catalysts to titanium catalysts is 3-5:1; the amount of catalyst added is 2-4wt% of the mass of the diol.

[0014] Antimony catalysts are highly active, especially antimony trioxide, which is cheap. However, trivalent antimony can be reduced to metallic antimony during polycondensation, which makes the film gray and foggy, and increases the haze. In addition, antimony catalysts are more toxic than titanium and tin catalysts. The use of the above-mentioned germanium catalyst and titanium catalyst compound catalyst system can reduce the occurrence of side reactions, and there is no need to add an additional anti-etherification agent, which is also a small molecule substance that produces precipitation.

[0015] Further, in step (S1), the esterification reaction conditions are as follows: after adding diol monomer, aromatic diacid monomer and catalyst into the reaction kettle, the esterification reaction is carried out at 230-240°C and 0.1-0.5Mpa, and after the water output reaches the theoretical value, the pressure is released to normal pressure; the vacuum polycondensation is carried out at 0.001-0.01MPa and 260-280°C, and when the intrinsic viscosity of the product obtained by the reaction system reaches 0.52-0.57dL·g -1 When adding, dipentaerythritol phosphate is added. The intrinsic viscosity of the product obtained by the reaction system refers to the intrinsic viscosity of the product obtained when the reaction is terminated at this time. When adding, the vacuum degree of the system is maintained, and the system is slowly added through a metering pump, and the addition is generally completed within 10-20 minutes.

[0016] Furthermore, in steps (S1) and (S2), post-treatment is well known in the art, and polyester masterbatch is obtained through melt pump extrusion, pelletizing, and drying, which is the core layer polyester raw material.

[0017] The inventor unexpectedly found that during the vacuum polycondensation process, adding a small amount of dipentaerythritol phosphate to the system can significantly improve the low molecular weight precipitation of the product polyester film, so that the product polyester film is placed at 150°C for 2 hours, and after being placed at double 85 high temperature and high humidity for 10 hours, the haze improvement value is very small. The inventor speculates that on the one hand, the presence of dipentaerythritol ester increases the crosslinking degree of the system during the vacuum polycondensation stage of polyester, and reduces the production of small molecular substances in subsequent melt extrusion and other stages; on the other hand, the presence of phosphate improves the oxidation resistance of the system and also reduces the phenomenon of small molecular substances produced by oxidation in subsequent melt extrusion and other stages. However, the inventor also found that the timing of adding dipentaerythritol phosphate needs to be strictly controlled. After a large number of experiments, it was found that during polycondensation, when the intrinsic viscosity of the system product reaches 0.52-0.57dL / g, adding dipentaerythritol phosphate can achieve the above purpose. The intrinsic viscosity of the system product reaches 0.52-0.57dL / g, which means that the reaction is stopped at this time, and the intrinsic viscosity of the product is 0.52-0.57dL / g. If the intrinsic viscosity of the system product is not within the above range, for example, when the intrinsic viscosity of the system product is lower than 0.5dL / g, dipentaerythritol phosphate is added too early, and the purpose of low precipitation cannot be fully achieved; when the intrinsic viscosity of the system product is greater than 0.57dL / g, dipentaerythritol phosphate is added too late, and the initial haze of the obtained polyester film is high and cannot meet the requirements.

[0018] Further, in step (S2), the intrinsic viscosity of the silicon-containing opening agent polyester chip is 0.5-0.7dL / g, the silicon dioxide content is 0.2-5wt%, and the silicon dioxide content is preferably 2-4wt%. Specifically, the silicon opening agent polyester chip is selected from at least one of Yizheng FG610 film-grade polyester chip, FG620 film-grade polyester chip, FG630 film-grade polyester chip, Zhejiang Yongsheng masterbatch YS-, and Yangzhou Youju polyester chip KM3-. The acrylic resin is preferably an organosilicon-modified acrylic resin, such as WH108A, SJ-804, S-611, and the acrylic resin solid content is 40-55%. The post-treatment is the same as step (S1) and is well known in the art.

[0019] Furthermore, in step (S3), the core layer polyester raw material is added to the feed port of the main screw extruder B, and the surface layer polyester raw material is added to the feed port of the auxiliary screw extruder A. The auxiliary screw extruder A has a distribution module, and the thickness of the intermediate core layer and the surface layer of the obtained polyester film is controlled by controlling the metering pump.

[0020] Furthermore, in step (S4), pre-crystallization is to control the crystallinity at 25-30%, drying is to control the moisture content below 30ppm, and longitudinal and transverse biaxial stretching is to first stretch longitudinally and then stretch transversely; the longitudinal stretching temperature is 80-105°C, and the longitudinal stretching ratio is 3.2-3.8; the transverse stretching temperature is 110-130°C, and the transverse stretching ratio is 3.2-3.8. Before stretching, it is preheated by an infrared heater, and the preheating temperature is 10-20°C lower than the stretching temperature. Heat setting, relaxation, cooling, pulling, and winding are conventional polyester film processes.

[0021] Furthermore, the polyester film obtained by the preparation method of the present invention is an ABA three-layer composite structure, wherein the ABA three-layer composite structure includes a thin film and a thick film, wherein the thickness of the middle layer B of the thin film is 10-40 μm, and the thickness of the surface layer A is 3-15 μm; the thickness of the middle layer B of the thick film is 40-180 μm, and the thickness of the surface layer A is 5-35 μm.

[0022] The polyester film obtained by the preparation method of the present invention has excellent performance and can be subjected to high temperature and / or high humidity at will, and the haze increase value is very low. It is very suitable for fields with high requirements for optical properties. The preparation method of the present invention can be completed on the basis of the original polyester masterbatch synthesis equipment, without adding additional large-scale expensive equipment and processes, and has the advantage of industrialization. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further explained below through specific embodiments.

[0024] Example 1

[0025] (S1) Ethylene glycol and terephthalic acid are added to a reaction kettle at a molar ratio of 1:1.1, and a composite catalyst is added at a mass ratio of 3 wt% of ethylene glycol, wherein the composite catalyst is a mixture of tetragonal germanium dioxide and tetrabutyl titanate at a mass ratio of 3:1. Esterification is performed at 230° C. and 0.2 MPa. After the water output reaches a theoretical value, the pressure is released to normal pressure. Thereafter, vacuum polycondensation is performed at 0.01 MPa, and the polycondensation temperature is 270° C. When the intrinsic viscosity of the product obtained by the reaction system is 0.52 dL·g -1 When adding 0.8wt% of dipentaerythritol phosphate by weight of ethylene glycol through a metering pump within 10 minutes, continuing vacuum polycondensation, after the reaction is completed, releasing the pressure, cooling, extruding the product through a melt pump, pelletizing, and drying to obtain a core layer polyester raw material;

[0026] (S2) Based on the total mass of the film-grade polyester chips FG610 and the acrylic resin WH108A being 100 wt%, 90 wt% of the film-grade polyester chips FG610 and 10 wt% of the acrylic resin WH108A are melt-extruded, pelletized, and dried to obtain a surface polyester raw material;

[0027] (S3) the core layer polyester raw material is added to the feed port of the main screw extruder B, and the surface layer polyester raw material is added to the feed port of the auxiliary screw extruder A for three-layer co-extrusion. The metering pump is controlled according to the polyester raw material mass ratio of 2:11:2 of A layer: B layer: A layer (i.e., surface layer: middle layer: surface layer). The operating temperature of the screw extruder is 230-270° C. After the melt is filtered through a filter screen, it is combined in a three-layer structure die head and extruded into a sandwich structure film. The polyester casting is cooled on a cooling roller to obtain an ABA type three-layer composite structure polyester masterbatch, wherein A is the surface layer polyester and B is the core layer polyester.

[0028] (S4) The composite structure polyester masterbatch is pre-crystallized to make the crystallinity of 25%, and dried to a moisture content of ≤30ppm. The slices are preheated at 85°C for 30 seconds by an infrared heater and stretched longitudinally at a temperature of 95°C and a longitudinal stretching ratio of 3.5. Then, they are preheated at 100°C for 30 seconds by an infrared heater and stretched transversely at a temperature of 115°C and a transverse stretching ratio of 3.5. The slices are heat-set, relaxed, cooled, pulled, and rolled at 220°C to obtain a low-precipitation and low-volatile polyester film. The polyester film has an ABA three-layer composite structure, wherein the thickness of the middle core layer B is about 110μm, the thickness of the surface layer A is about 20μm, and the total thickness of the polyester film is about 150μm.

[0029] Example 2

[0030] The other conditions are the same as those in Example 1, except that in step (S1), when the intrinsic viscosity of the product obtained by the reaction system is 0.57 dL·g -1 When the reaction mixture was stirred for 10 min, dipentaerythritol phosphate in an amount of 0.5 wt% of the mass of ethylene glycol was added through a metering pump within 10 min.

[0031] Example 3

[0032] The other conditions are the same as those in Example 1, except that in step (S1), when the intrinsic viscosity of the product obtained by the reaction system is 0.55 dL·g -1 When the reaction mixture was stirred for 10 min, dipentaerythritol phosphate (0.65 wt% of the mass of ethylene glycol) was added through a metering pump within 10 min.

[0033] Example 4

[0034] The other conditions are the same as those in Example 1, except that step (S2) is changed to: 80 parts by weight of film-grade polyester chips FG620 and 20 parts by weight of acrylic resin WH108A are melt-extruded, pelletized, and dried to obtain a surface polyester raw material.

[0035] Comparative Example 1

[0036] The other conditions are the same as those in Example 1, except that in step (S1), when the intrinsic viscosity of the product obtained by the reaction system is 0.50 dL·g -1When the reaction mixture was stirred for 10 min, dipentaerythritol phosphate in an amount of 0.8 wt% of the mass of ethylene glycol was added through a metering pump within 10 min.

[0037] Comparative Example 2

[0038] The other conditions are the same as those in Example 2, except that in step (S1), when the intrinsic viscosity of the product obtained by the reaction system is 0.60 dL·g -1 When the reaction mixture was stirred for 10 min, dipentaerythritol phosphate in an amount of 0.5 wt% of the mass of ethylene glycol was added through a metering pump within 10 min.

[0039] Comparative Example 3

[0040] The other conditions are the same as those in Example 1, except that in step (S1), when the intrinsic viscosity of the product obtained by the reaction system is 0.52 dL·g -1 When the mixture was stirred for 10 min, 0.8 wt% of dipentaerythritol by weight of ethylene glycol was added through a metering pump within 10 min.

[0041] Comparative Example 4

[0042] The other conditions are the same as those in Example 1, except that in step (S1), after esterification and before vacuum polycondensation, dipentaerythritol phosphate in an amount of 0.8 wt % of the mass of ethylene glycol is added to the system.

[0043] Application Examples

[0044] The polyester films obtained in the above examples and comparative examples were tested for performance, and the haze was tested using a German BYK transmission haze meter. The results are shown in Table 1 below.

[0045] Table 1 Polyester film performance test

[0046]

[0047] It can be seen from the data in Table 1 that the ABA three-layer composite structure polyester film prepared by the preparation method of the present invention has a haze increase value of <0.3% after heat treatment at 150°C for 2 hours or double 85 high temperature and high humidity aging treatment for 20 hours, indicating that the preparation process of the present invention can give the polyester film the characteristics of low precipitation and low volatility.

Claims

1. A method for preparing a low-precipitation and low-volatile polyester film, characterized in that: The following steps are involved: (S1) esterifying the diol monomer and the aromatic diacid monomer in the presence of a catalyst, followed by vacuum polycondensation, and in the polycondensation stage, when the intrinsic viscosity of the system product reaches 0.52-0.57 dL / g, adding 0.5-0.8 wt% of dipentaerythritol phosphate by weight of the diol monomer, and obtaining a core layer polyester raw material after post-treatment; (S2) based on the total mass of the silicon-containing opening agent polyester chips and the acrylic resin being 100wt%, 80-90wt% of the silicon-containing opening agent polyester chips and 10-20wt% of the acrylic resin are melt-extruded, and after post-treatment, a surface polyester raw material is obtained; (S3) adding the core layer polyester raw material and the surface layer polyester raw material into a melt extruder respectively, and performing three-layer co-extrusion to obtain an ABA type three-layer composite structure polyester masterbatch, wherein A is the surface layer polyester and B is the core layer polyester; (S4) The composite structure polyester masterbatch is pre-crystallized, dried, biaxially stretched in the longitudinal and transverse directions, heat-set, relaxed, cooled, pulled, and rolled to obtain a low precipitation and low volatility polyester film.

2. The preparation method according to claim 1, characterized in that: In step (S1), the diol monomer is selected from at least one of hexylene glycol, cyclohexanediol, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and neopentyl glycol, and the aromatic diacid monomer is selected from at least one of terephthalic acid, naphthalene dicarboxylic acid, and biphenyl dicarboxylic acid.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the diol monomer to the aromatic diacid monomer is 1-1.2:1-1.2, and preferably the molar ratio of the diol monomer to the aromatic diacid monomer is 1:1-1.

2.

4. The preparation method according to claim 1, characterized in that: In step (S1), the catalyst is selected from antimony catalysts (antimony trioxide, antimony acetate), titanium catalysts (tetrabutyl titanate, tetraethyl titanate, tetrapropyl titanate and tetraisopropyl titanate) and germanium catalysts (tetragonal germanium dioxide), tin catalysts (monobutyl tin oxide, monobutyl tin triisooctoate, stannous octoate, dibutyl tin diacetate, dibutyl tin dilaurate); preferably, the amount of catalyst added is 2-4wt% of the mass of the glycol.

5. The preparation method according to claim 4, characterized in that: The catalyst is a mixed catalytic system of a germanium catalyst and a titanium catalyst; preferably, the mass ratio of the germanium catalyst to the titanium catalyst is 3-5:1; and the amount of the catalyst added is 2-4wt% of the mass of the diol.

6. The preparation method according to claim 1, characterized in that: In step (S1), the esterification reaction conditions are as follows: after adding diol monomer, aromatic diacid monomer and catalyst into the reaction kettle, the esterification reaction is carried out at 230-240° C. and 0.1-0.5 MPa, and after the water output reaches the theoretical value, the pressure is released to normal pressure; the vacuum polycondensation is carried out at 0.001-0.01 MPa and 260-280° C., and when the intrinsic viscosity of the product obtained by the reaction system reaches 0.52-0.57 dL·g -1 When adding dipentaerythritol phosphate.

7. The preparation method according to claim 1, characterized in that: In step (S2), the intrinsic viscosity of the silicon-containing opening agent polyester chip is 0.5-0.7 dL / g, the silicon dioxide content is 0.2-5wt%, preferably, the silicon dioxide content is 2-4wt%; the acrylic resin is an organic silicon modified acrylic resin, and the solid content of the acrylic resin is 40-55%.

8. The preparation method according to claim 1, characterized in that: In step (S3), the core layer polyester raw material is added to the feed port of the main screw extruder, and the surface layer polyester raw material is added to the feed port of the auxiliary screw extruder, and the feeding amount of the main screw extruder is controlled by a metering pump.

9. The preparation method according to claim 1, characterized in that: In step (S4), pre-crystallization is to control the crystallinity at 25-30%, drying is to control the moisture content below 30 ppm, and longitudinal and transverse biaxial stretching is to first perform longitudinal stretching and then transverse stretching; the longitudinal stretching temperature is 80-105°C, and the longitudinal stretching ratio is 3.2-3.8; the transverse stretching temperature is 110-130°C, and the transverse stretching ratio is 3.2-3.

8.

10. The preparation method according to claim 1, characterized in that: The obtained polyester film is an ABA three-layer composite structure; preferably, the ABA three-layer composite structure includes a thin film and a thick film, the thickness of the middle layer B of the thin film is 10-40 μm, and the thickness of the surface layer A is 3-15 μm; The thickness of the middle layer B of the thick film is 40-180 μm, and the thickness of the surface layer A is 5-35 μm.

Citation Information

Cited By

  • Colored polyester film for lithium battery termination adhesive tape

    CN120620811A

  • Colored polyester film for lithium battery termination tape

    CN120620811B